Eriophyoid studies in Turkey: review and perspectives - Denizhan, Evsel; Szydło, Wiktoria; Skoracka, Anna (Biological Letters, 2014)
Although the geographical location and botanical history of Turkey make the country a perfect place for a potentially rich diversity of eriophyoid mites, little is known about the Turkish eriophyoid fauna. The current paper is a brief review of the existing records of eriophyoid mites found so far in Turkey, with additional information on 6 grass-associated eriophyoid species recorded recently. The 134 eriophyoid species collected in Turkey come from only ca. 1.2% of all Turkish plant species. The role of collecting ecological and molecular data and studying economically significant eriophyoid mites species in this area is particularly stressed.